2016
DOI: 10.1515/jomb-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Thyroid-stimulating Hormone as an Indicator for Assessment of Iodine Status in the Republic of Macedonia

Abstract: SummaryBackgroundIodine deficiency is associated with goiter and impaired brain function leading to cretinism. An increased frequency of thyroid-stimulating hormone (TSH) measurements above 5 mlU/L on newborn screening points toward an impaired iodine status of the population.MethodsA 13-year retrospective analysis was performed in 228,266 newborns participating in the national thyroid newborn screening program. The TSH concentration was measured in dry blood spots collected by heel stick on filter paper, 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
3
1
1
Order By: Relevance
“…Although these studies used ultrasound to rule out non-obvious or potential abnormalities of the thyroid gland, this should not be the reason for non-compliance with our results, because there are no recommendations for necessary ultrasound examination of the thyroid gland by the NACB ( 6 ). Our results are not similar to the results of studies in which ultrasound was not used for the assessment of patients’ health status ( 21 , 22 ). The reference values of thyroid hormones are dependent on the population, methodology and apparatus on which the analysis is performed, as our study confirmed ( 23 26 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although these studies used ultrasound to rule out non-obvious or potential abnormalities of the thyroid gland, this should not be the reason for non-compliance with our results, because there are no recommendations for necessary ultrasound examination of the thyroid gland by the NACB ( 6 ). Our results are not similar to the results of studies in which ultrasound was not used for the assessment of patients’ health status ( 21 , 22 ). The reference values of thyroid hormones are dependent on the population, methodology and apparatus on which the analysis is performed, as our study confirmed ( 23 26 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in accordance with our finding that 4.44% of the screened newborns in the Vardar region had a TSH concentration above 5 mIU/L whole blood, as an indicator of iodine deficiency, in comparison with the Eastern region where only 1.66% of newborns had TSH>5 mIU/L. Possible mild iodine deficiency in the Vardar region has been described previously [23]. Iodine intake at the population level is a major determinant of thyroid function, and decreasing intake is reflected in increasing neonatal TSH levels [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to iodine deficiency, although Macedonia as a whole is no longer recognized as an iodine-deficient area [22]. However, some regions might still belong to iodine-deficient areas [23]. This is in accordance with our finding that 4.44% of the screened newborns in the Vardar region had a TSH concentration above 5 mIU/L whole blood, as an indicator of iodine deficiency, in comparison with the Eastern region where only 1.66% of newborns had TSH>5 mIU/L.…”
Section: Discussionmentioning
confidence: 99%
“…( 3 ). A recently published study accessing the iodine status through TSH measurements on newborn screening reported iodine sufficiency in Macedonia ( 21 ). Considering these facts the etiology of the most of our TCH cases remains unknown.…”
Section: Discussionmentioning
confidence: 99%